A Combined Numerical and Experimental Study of Heat Transfer in a Roughened Square Channel with 45∘ Ribs - M. E. Taslim; H. Liu (International Journal of Rotating Machinery)
Experimental investigations have shown that the enhancement in heat transfer coefficients for air flow in a channel roughened with low blockage (e/Dh<0.1) angled ribs is on the average higher than that roughened with 90∘ ribs of the same geometry. Secondary flows generated by the angled ribs are believed to be responsible for these higher heat transfer coefficients. These secondary flows also create a spanwise variation in the heat transfer coefficient on the roughened wall with high levels of the heat transfer coefficient at one end of the rib and low levels at the other end. In an effort to investigate the thermal behavior of the angled ribs at elevated Reynolds numbers, a combined numerical and experimental study was conducted. In the numerical part, a square channel roughened with 45∘ ribs of four blockage ratios (e/Dh) of 0.10,0.15,0.20, and 0.25, each for a fixed pitch-to-height ratio (P/e) of 10, was modeled. Sharp as well as round-corner ribs (r/e=0 and 0.25) in a staggered arrangement were studied. The numerical models contained the smooth entry and exit regions to simulate exactly the tested geometries. A pressure-correction-based, multiblock, multigrid, unstructured/adaptive commercial software was used in this investigation. Standard high Reynolds number k−ε